Perception of active methodologies by teachers working in the State of Minas Gerais, Brazil (Research, Society and Development, 2021)
Technologies are incorporated in different areas of our daily lives, this technological social scenario, seen outside of schools, is opposed to daily school life, as most Brazilian schools have a traditional and low-tech curriculum. In this context, it is necessary that education adapts to innovation and technology, for this, teachers need to be well-trained and encouraged to apply active, attractive and technology-integrated teaching methods. The research evaluated the perception of active methodologies by teachers working in the State of Minas Gerais. The data were obtained from the responses of 485 teachers via electronic form in the year 2020. About the knowledge of active methodologies, 82.1% knew some methodology, being more familiar with seminar (57.2%), project-based learning/ problems (51%) and inverted classroom (45.7%). Only 20.8% were trained during graduation, and only 23.3% received training from the institution where they work. About/Regarding/Concerning the respondents, 51.6% do not receive an incentive to use the methodologies and report that the main challenges are the lack of training (68%), planning time (48.5%), lack of teaching equipment (48.5%), runtime (42.7%) and student participation (40.2%). Although 79.2% of the respondents did not receive training undergraduate course, most of them considered its inclusion relevant, reflecting the need to modernize the curriculum.